Left Atrial Appendage Occlusion Complicated by Appendage Perforation Rescued by Device Deployment. (September 2018) - Sarcon, Anna; Roy, Dipayon; Laughrun, David; Huntsinger, Mary; Schwartz, Jacqueline; Sohn, Jina; Doshi, Rahul N.
The Watchman device is a transcatheter left atrial appendage (LAA) occluding device used in patients with nonvalvular atrial fibrillation (NVAF) and a high CHADS2-VA2SC score who are poor long-term anticoagulation candidates. Pericardial effusion related to device deployment and perforation can be a life-threatening complication. While not common in hands of experienced operators, management may require surgical intervention. Here we present a rare case of LAA perforation, which was corrected by successful repositioning of the device foregoing the need for surgical management.